Computation of contribution from the cavity effect to protein-ligand binding free energy - Grigoriev, F.V.; Jabin, S.N.; Sulimov, V.B.; Romanov, A.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2008)
Some results of the study of the cavitation effect, which provides an essential part of hydrophobic interactions due to the formation of protein-ligand complexes, are discussed. The change of the cavitation free energy is calculated for three protein-ligand complexes using the thermodynamic integration procedure with the original algorithm for growing the interaction potential between the cavity and the water molecules. The thermodynamic cycle consists of two stages: annihilation of the cavity of the ligand at the unbound state and its creation at the active site of the protein (the bound state). It is found that, for all the complexes under study, the values are negative and favorable for binding. The main contribution to the cavitation effect is due to the annihilation of the cavity of the ligand. All computations were made using a parallel version of the CAVE code.